Adherence to opioid therapy in patients with chronic non-cancer pain attending a pain clinic in Malaysia - Mizhar, Hussam; Zin, Che Suraya; Abdullah Sani, Asween Rowena; Mohamed, Abdul Hadi; H. Ling, Tan; M. Izzat, Munira (2018)
Objectives: This study examined the adherence to opioid therapy in patients with chronic non-cancer pain (CNCP). The prevalence of opioid use and pain scores was also explored. Methods: This cross-sectional study was conducted among patients with non-cancer pain attending a pain clinic at a tertiary hospital in Malaysia from August 2016 to February 2017. All patients prescribed with any of the five available opioids (morphine, oxycodone, fentanyl, buprenorphine, and dihydrocodeine) were included in the study and their medical and prescription records were assessed for further information on opioid use such as the type of opioid, dose, frequency and duration. Prevalence of opioid use was calculated by dividing the number of opioid users and the total number of patients attending the pain clinic during the study period. Adherence was calculated for patients with long-term opioid therapy (> 90 days per year) and measured using the Medication Possession Ratio (MPR). This was derived by sum up the total days covered with medication in the last 365 days, and then divide that by the total days the medication was prescribed over the same period. A cutoff point of 80% or more was considered as adherence. Pain intensity score was assessed through a numerical scale from 0 (no pain)-10 (worst possible pain) at 4 different points (now, on average, least in the last 24h, worst in the last 24h). Results: A total of 555 patients with various non-cancer pain conditions attended the pain clinic during the study period. Prevalence of opioid use among these patients was 13.5% (n=74/555). Of these, 24.3% (n=18/74) patients using opioids for long-term (>90days) and were included in the adherence measure. Seventy-eight percent (n=14/18) of these long-term opioid users were adherent to opioid therapy with a reported MPR >80%. Twenty-two percent (n=4/18) showed non-adherence to opioid therapy with a reported MPR <80%. The mean pain score for both adherent and non-adherent groups was 5/10 and there was no statistical difference between the two groups. Conclusion: The preliminary results of this study demonstrated that the majority of patients with chronic opioid use adhered to their prescribed opioids. The prevalence of opioid use among patients with non-cancer pain was low and the number of patients using opioid for the long term was ~20% which is similar to the finding from the previous study. Future research is required to evaluate the clinical outcomes in patients with CNCP using opioid for long-term, particularly in non-adherent patients.